2018
DOI: 10.22606/afse.2018.23001
|View full text |Cite
|
Sign up to set email alerts
|

Biscuits: A Substitution of Wheat Flour with Purple Rice Flour

Abstract: Biscuits are excellent snacks with a long shelf life. However, they are also high-energy foods so there is a great need to improve their nutrient value. Many substitutions of composite flours for wheat flour have been studied in order to reduce their potential negative impact on human health. Whole purple rice flour is a novel flour with high antioxidant contents and dietary fiber. However, the partial replacement of wheat flour with purple rice flour can affect the physicochemical properties and consumer pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 120 publications
(167 reference statements)
3
22
0
1
Order By: Relevance
“…A similar decreasing trend was observed by Klunklin and Savage (2018) who reported that, colour decreased by increasing the addition of purple rice flour, were in control was 6.09, decreased to 6.00 , 5.83 , 5.71 and 5.02 in sample with 25, 50, 75 and 100% PRF. Overall acceptability decreased significantly by increasing the addition of purple rice flour, were in control was 6.14, decreased to 5.…”
supporting
confidence: 86%
“…A similar decreasing trend was observed by Klunklin and Savage (2018) who reported that, colour decreased by increasing the addition of purple rice flour, were in control was 6.09, decreased to 6.00 , 5.83 , 5.71 and 5.02 in sample with 25, 50, 75 and 100% PRF. Overall acceptability decreased significantly by increasing the addition of purple rice flour, were in control was 6.14, decreased to 5.…”
supporting
confidence: 86%
“…The texture, flavor, and appearance of the biscuits are major attributes that affect biscuit acceptability (Torbica et al, 2012). Black rice flour (gluten-free) suitable to prepare products for celiac disease (Klunklin and Savage, 2018). There is a high demand to use natural antioxidants in foods to enhance the shelf life of biscuits.…”
Section: Sensory Evaluation Of Cooked Rice:-mentioning
confidence: 99%
“…The traditional method of making biscuit dough is to use semi-solid fat at room temperature [5]. Briefly, biscuits are high-energy, easily digestible foods based mostly on wheat flour, oil and sugar [6,7]. The high calorie content of the biscuits disrupts the balanced diet of the consumer.…”
Section: Introductionmentioning
confidence: 99%